PENINGKATAN DAYA SAING PRODUKSI LADA INDONESIA MELALUI ADOPSI INOVASI - Agus Wahyudi, MS; Ekwasita Rini Pribadi (Perspektif, 2016)
In the last five years the price of pepper world was increasing rapidly, in 2010 the export price of black pepper and white pepper Indonesia respectively were FOB US $ 3,677 and FOB US $ 5,662 be FOB US $ 8,975 and FOB US $ 12,362 per metric ton in the year 2014. Nevertheless, Indonesian pepper production has declined, namely 59,000 tonnes in 2010 to 52,000 tons in 2014. This reflects the constraints that limit the development of pepper production in Indonesia. Indonesian pepper internally has a competitive advantage in the factor of natural resources and the availability of human resources, but there are weakness in the quality of the labour, especially in the application and knowledge of cultivation technology and the use of superior seeds. To improve the competitiveness of Indonesian pepper, it is necessary to improve the quality and quantity of production by increasing productivity through improvement methods of cultivation that is environmentally friendly, use of certified seeds and high quality input grade, primary product processing that refers to the quality standards, accompanied by the introduction of institutional innovation and technical cultivation with the active role of farmer groups. Due to the successful adoption of the technology depends on knowledge of the perpetrators of farming technologies that will be developed.